2010
DOI: 10.1002/pbc.22901
|View full text |Cite
|
Sign up to set email alerts
|

Mannose‐binding lectin (MBL) and the risk for febrile neutropenia and infection in pediatric oncology patients with chemotherapy

Abstract: MBL deficiency could not be identified as an independent risk factor for FN or infection in pediatric oncology patients. A multicenter study of children with comparable chemotherapy regimens, relevant and equal outcome definitions and measuring both MBL levels and genotypes, will be required to avoid clinical and methodological inconsistencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…In the review by Frakking et al [22] investigating the correlation of infection in pediatric oncology patients with MBL deficiency and/or severity of infection, no relationship was found between low MBL levels and presence of sepsis, bacteremia, or fungal infection in 3 of the 5 studies, while the results of the other 2 studies were to the contrary. Although there are a variety of studies with different results in the literature [23,24,25,26,27], Peterslund et al [28] showed a significant correlation between low levels of MBL and the development of bacteremia in adult patients with hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the review by Frakking et al [22] investigating the correlation of infection in pediatric oncology patients with MBL deficiency and/or severity of infection, no relationship was found between low MBL levels and presence of sepsis, bacteremia, or fungal infection in 3 of the 5 studies, while the results of the other 2 studies were to the contrary. Although there are a variety of studies with different results in the literature [23,24,25,26,27], Peterslund et al [28] showed a significant correlation between low levels of MBL and the development of bacteremia in adult patients with hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The dramatic differences reported in the studies of Peterslund et al [28], Neth et al [29], and Schlapbach et al [23] in median MBL concentrations were virtually identical to those of the other patient categories. The studies of Klostergaard et al [27], Frakking et al [22], and Schlapbach et al [23] revealed that infections due to gram-positive bacteria were more commonly observed in cases with low MBL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular viral sensors have long been recognized as crucial mediators of innate antiviral defense with important effects on the magnitude and quality of both innate and adaptive immune responses. Important antiviral factors and pathways, such as the retinoic acid-inducible gene I protein/DEAD (Asp-Glu-Ala-Asp) box polypeptide 58 (RIG-I/DDX58), Toll-like receptors (TLRs), mannose-binding lectin (encoded by MBL2 ), and dendritic cell−specific intercellular adhesion molecule-3−grabbing non-integrin (DC-SIGN, also known as CD209) play a role in viral sensing, control, pathogenesis, and outcome of viral infections (Thompson and Iwasaki 2008; Nakhaei et al 2009; Faure and Rabourdin-Combe 2011; Frakking et al 2011; Clingan et al 2012). …”
mentioning
confidence: 99%
“…(4, 11, 12, 16, 19, 33–38) We did find that MBL levels were diluted in patients that received extremely high volumes of fluid in the first 24 hours; a common occurrence in patients with severe sepsis that could possibly confound the relationship between MBL levels and infection-related critical illness. MBL levels were strongly genetically influenced by the combination of high, intermediate and low producing haplotypes.…”
Section: Discussionmentioning
confidence: 88%